Association Between Lipid Profile and Glyceamic Control in Sudanese Children with Type 1 Diabetes Mellitus at Gezira State, Sudan - A Hamza, Mohammed; E. Khalid, Khalid; K Saeed, Osman; M Haroun, Huda (مجلة الجزيرة للعلوم الصحية; مجلد 14 عدد 2 (2018), 2018)
Introduction: Diabetes mellitus describes a metabolic disorder of multiple aetiology characterized by chronic hyperglycemia with disturbances of carbohydrate, fat and protein metabolism resulting from defects in insulin secretion, insulin action, or both. Objectives This study aimed to assess the metabolic control of type 1 diabetes mellitus (T1DM) in Sudanese children. Methods: One hundred and seventy four children with type 1 diabetes mellitus were enrolled in this study; 56 healthy non-diabetic children served as a control group. Glycosylated hemoglobin (HbA1c), total cholesterol (TC), triacylglycerol (TG), low density lipoprotein-cholesterol (LDL-C), high density lipoprotein-cholesterol (HDL-C) were measured, very low density lipoprotein-cholesterol (VLDL), and LDL-C/HDL-C ratio were calculated. Results : HbA1c,TC, LDL-C LDL-C/HDL-C ratio and TG were significantly higher among diabetic group compared to non-diabetic group (P<0.001 and P<0.05 for TG).In the diabetic group, there was a positive significant correlation of: HbA1c with TC, TG, HDL- C, LDL-C, VLDL and LDL/HDL ratio; TC with TG, HDL- C, LDL-C, VLDL and LDL/HDL; TG with LDL- C, VLDL and LDL/HDL ratio; HDL-C with LDL-C;LDL-C with VLDL and LDL/ HDL;VLDL-C with LDL/HDL ratio. A significant negative correlation was observed between HDL- C and LDL/HDL ratio. Diabetic group with poor metabolic control (HbA1c level >8).had significantly higher levels of TC and LDL-C (P<0.001),TG and VLDL (P<0.01), HDL-C and LDL-C/ HDL-C ratio (P<0.05) compared with diabetic group with good metabolic control (HbA1c <8%). Conclusion: 85.63% of diabetic patients were found to have poor metabolic control (HbA1c level >8). يوصف مرض السكري بأنه من المسببات المرضية المتعددة التي تتميز بفرط  سكر الدم المزمن واضطراب في التمثيل الغذائي ( اضطرابات من الكربوهيدرات والدهون واستقلاب البروتين) الناتج عن نقص في إفراز الأنسولين، عمل الانسولين أو كليهما.هدفت هذه الدراسة لاستخدام التقييم الكيموحيوي لمعرفة مدي التحكم لضبط السكر عند مرضي السكري النوع الاول. إشتملت هذه الدراسه علي 174طفل مصابين مرض السكري و56 أصحاء من نفس العمر.تضمنت هذه الدراسة  القياسات الكيموحيويه الأتيه: خضاب الدم المسكر، الكوليستيرول ، ثلاثي أسيل الجليسرول و الكوليستيرول المرتبط  بالبروتينات الشحميه منخفضة وعاليه الكثافة والبروتينات الشحميه المنخفضة جدا ونسبة البروتينات الشحميه منخفضة الكثافة الي البروتينات الشحميه عالية الكثافة. وجد أن تركيز كل من خضاب الدم المسكر، الكوليستيرول ، الكوليستيرول المرتبط  بالبروتينات الشحميه منخفضة الكثافة ونسبة البروتينات الشحميه منخفضة الكثافة الي البروتينات الشحميه عالية الكثافة وثلاثي أسيل الجليسرول يرتفع إرتفاعا ذا معني عند مجموعة مرضي السكري.مستوي خضاب الدم المسكر يرتبط إرتباطا موجبا ذا معني مع كل من الكوليستيرول ، ثلاثي أسيل الجليسرول والبروتينات الشحميه عالية ومنخفضة الكثافة والبروتينات الشحميه المنخفضة جدا ونسبة البروتينات الشحميه منخفضة الكثافة الي البروتينات الشحميه عالية الكثافة، الكوليستيرول مع كل من ثلاثي أسيل الجليسرول والبروتينات الشحميه عالية و منخفضة الكثافة والبروتينات الشحميه المنخفضة جدا ونسبة البروتينات الشحميه منخفضة الكثافة الي البروتينات الشحميه عالية الكثافة ، يرتبط ثلاثي أسيل الجليسرول مع كل من البروتينات الشحميه منخفضة الكثافة والبروتينات الشحميه المنخفضة جدا ونسبة البروتينات الشحميه منخفضة الكثافة الي البروتينات الشحميه عالية الكثافة . كما أن  مستوي البروتينات الشحميه عالية الكثافة يرتبط إرتباطا ذا معني مع نسبة البروتينات الشحميه منخفضة الكثافة الي البروتينات الشحميه عالية الكثافة.طبقا لتقسيم مجموعة الدارسين لمرض السكري العالميه الأمريكيه أظهرت هذه الدراسه أن نسبة (85.63)  من المرضي يبلغ معدل خضاب الدم المسكر عندهم أكثر من  8% (ضبط غير مقبول) بينما  (%14.37) يبلغ معدل خضاب الدم المسكر عندهم أقل من  8% (ضبط مقبول).  وجدت هذه الدراسة ان مرضي السكري والذين لديهم ضبط غير مقبول لخضاب الدم المسكر ترتفع عندهم مستويات الكوليستيرول ، ثلاثي أسيل الجليسرول و الكوليستيرول المرتبط  بالبروتينات الشحميه منخفضة وعاليه الكثافة والبروتينات الشحميه المنخفضة جدا ونسبة البروتينات الشحميه منخفضة الكثافة الي البروتينات الشحميه عالية الكثافة ارتفاعا ذا معني مقارنة مرضي السكري والذين لديهم ضبط مقبول لخضاب الدم المسكر.